Breast Cancer in Adolescent and Young Adult Women Under the Age of 40 Years. Issue 6 (June 2021) - Cathcart-Rake, Elizabeth J.; Ruddy, Kathryn J.; Bleyer, Archie; Johnson, Rebecca H.
Abstract : In the United States, one in 196 women is diagnosed with breast cancer under the age of 40 years. Adolescents and young adults (AYAs), of age 15-39 years at diagnosis, experience a number of unique challenges when confronting breast cancer. The incidence of invasive breast cancer has increased among AYA women in the United States since 2004, and most of this change is due to an increase in young women diagnosed with distant disease. AYAs are more likely than older women to present with aggressive subtypes and advanced disease, and they often require systemic staging at diagnosis. Clinical trials should be considered whenever possible, particularly in AYAs with locally advanced or metastatic disease at diagnosis and those with disease progression or recurrence. A significant proportion of AYAs carry germline cancer predisposition mutations, which necessitates prompt genetic testing for all AYAs at diagnosis and may influence choice of local therapy. Suppression of ovarian function, as an adjunct to chemotherapy, may improve breast cancer survival in AYAs. To provide optimal care for AYAs with breast cancer, clinicians should engage multidisciplinary teams that offer fertility preservation, genetic counseling, physical and occupational therapy, nutrition, and psychosocial support, along with medical expertise in tailoring cancer-directed therapy and symptom management toward young women.